N, P-doped multiphase transition metal sulfides are used for efficient electrocatalytic oxygen evolution reaction - Zhang, Zhiqiang; Tang, Shuli; Lin, Xiaofeng; Liu, Chenghao; Hu, Shirong; Huang, Qitong (Applied surface science, 2022)
[Display omitted] •The N, P-Co9S8/CoS2/Co1-xS composite is first fabricated by atmosphere conversion pyrolysis strategy.•The catalyst exhibites more excellent OER performance than the RuO2 in alkaline solutions.•The multi-active components coupling tuning optimizes the valence orbitals and enhances the catalytic activity. It is of great significance for the electrolysis of hydrogen and air–fuel cells to synthesize super active non-noble-metal electrocatalytic oxygen evolution reaction (OER). Due to the limitation of the OER process involving multiple electron transfer and multiple intermediates. Catalysts with a single active component can hardly exhibit high activity in this process. Here, we report an N, P-doped multiphase transition metal sulfide composite electrocatalyst (N, P-Co9S8/CoS2/Co1-xS) by an atmosphere conversion pyrolysis strategy. The multiple active components not only provide abundant catalytic active sites for the reaction at the catalytic interface but also the coupling tuning of the heterogeneous interface optimizes the valence orbital of the catalyst, which results in the catalyst exhibiting excellent catalytic activity. Both theoretical calculations and experimental investigations confirm the excellent adsorption kinetics of the intermediates at the interface. When used as an electrocatalyst for OER in alkaline environments, it exhibits robust activity (η10: 285 mV, Tafel slope: 70 mV dec−1) and long-term stability. Our study illustrates that compared with single-component cobalt-based sulfide, N, P-Co9S8/CoS2/Co1-xS catalyst is favorable as highly efficient OER catalytic activity.